2018
DOI: 10.1021/acs.jpcc.8b08914
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional, Ordered, Double Transition Metal Carbides (MXenes): A New Family of Promising Catalysts for the Hydrogen Evolution Reaction

Abstract: Generation of hydrogen by splitting water with the electrocatalytic approach could become a more sustainable way following the discovery of new materials, such as the 2D transition-metal carbides. Developing eco-friendly, low-cost, stable, and highly active nonprecious hydrogen evolution reaction (HER) catalysts is one of key factors for hydrogen energy economy. Two-dimensional metal carbide and nitride (MXenes) materials have shown characteristics of promising HER catalysts. Herein, we explored the conductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 62 publications
2
77
0
Order By: Relevance
“…The results demonstrate that the ΔGH* of TM‐modified Mo 2 CO 2 is generally larger in value than that of the pure Mo 2 CO 2 (except for Ni at 12.5 % ML coverage), which implies that the former presents weaker interaction between H and O. It is generally accepted that the |ΔGH* |<0.2 eV represents the promising HER activity [28] . Based on this threshold criteria (highlighted by the grey area in Figure 5d), the surface‐modification of Mo 2 CO 2 with 12.5 %−V, 12.5 %−Cr, 12.5 %−Mn, 12.5 %−Fe, 16.7 %−Fe, 16.7 %−Co, 16.7 %−Ni and 16.7 %−Cu are potentially active electrocatalysts for HER (the corresponding ΔGH* are 0.13, −0.18, 0.08, −0.08, 0.19, 0.13, −0.17, and 0.16 eV, respectively).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The results demonstrate that the ΔGH* of TM‐modified Mo 2 CO 2 is generally larger in value than that of the pure Mo 2 CO 2 (except for Ni at 12.5 % ML coverage), which implies that the former presents weaker interaction between H and O. It is generally accepted that the |ΔGH* |<0.2 eV represents the promising HER activity [28] . Based on this threshold criteria (highlighted by the grey area in Figure 5d), the surface‐modification of Mo 2 CO 2 with 12.5 %−V, 12.5 %−Cr, 12.5 %−Mn, 12.5 %−Fe, 16.7 %−Fe, 16.7 %−Co, 16.7 %−Ni and 16.7 %−Cu are potentially active electrocatalysts for HER (the corresponding ΔGH* are 0.13, −0.18, 0.08, −0.08, 0.19, 0.13, −0.17, and 0.16 eV, respectively).…”
Section: Resultsmentioning
confidence: 85%
“…It is generally accepted that the j DG H* j < 0.2 eV represents the promising HER activity. [28] Based on this threshold criteria (highlighted by the grey area in Figure 5d), the surface-modification of Mo 2 CO 2 with 12.5 %À V,12.5 %À Cr,12.5 %À Mn,12.5 %À Fe,16.7 %À Fe,16.7 %À Co,16.7 %À Ni and 16.7 %À Cu are potentially active electrocatalysts for HER (the corresponding DG H* are 0. 13, À 0.18, 0.08, À 0.08, 0.19, 0.13, À 0.17, and 0.16 eV, respectively).…”
Section: Transition Metal Modificationmentioning
confidence: 99%
“…The electrocatalytic activity of MXenes is closely related to their oxygen-containing groups [187]. energy and hydrogen Gibbs free energy showed that increasing the number of electrons obtained by the end group oxygen enhanced the electrocatalytic performance.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…[126] It was also proved through DFT calculations that Cr 2 TiC 2 O 2 , Cr 2 VC 2 O 2 , Mo 2 TiC 2 O 2 , and Mo 2 VC 2 O 2 could exhibit excellent HER activity with surface oxygen atoms as the active sites. [127] Moreover, another extensively adopted strategy to improve the electrocatalysis property was heteroatom doping [128] or composite with other materials. [129] In 2018, Wang and co-workers reported the Mo 2 TiC 2 T x nanosheets with abundant surface Mo vacancies (V Mo ) by electrochemical exfoliation (Mo 2 TiC 2 T x -V Mo ), in which the Mo vacancies could act as the anchoring sites for single Pt atoms (Mo 2 TiC 2 T x -Pt SA ).…”
Section: Catalysts Based On Mxenesmentioning
confidence: 99%